The effect of synthetic conditions on piezoresistive properties of ultrasensitive carbon nanotube/PDMS 3D composites. (3rd January 2023) - Turco, Antonio; Monteduro, Anna Grazia; Montagna, Francesco; Primiceri, Elisabetta; Frigione, Mariaenrica; Maruccio, Giuseppe
Abstract: Carbon nanotube polymeric composites are widely developed as piezoresistive sensors. Despite these materials showed improved mechanical stability, they are less sensible than carbon aerogel. Moreover, the piezoresistive properties of these nanocomposites cannot be tuned to adapt the sensor to the different applications. Here we observed as modifying solvent dilution in the hard template synthetic route, allow for the fabrication of porous piezoresistive nanocomposites with different limits of detection, working ranges and sensitivities. More in details three different foams with diverse features were produced. Although all the three materials presented outstanding performances, the porous material prepared at higher dilution showed an incredible limit of detection for displacement (∼50 nm) and pressure (0.2 Pa) that are respectively 2.6 and 10 times lower than that recorded at lower prepolymer dilutions. However lower dilutions allow to produce sensors able to monitor larger pressures ranges (up to ∼150 kPa), which are 3 times higher than that of recorded in composites prepared at higher dilutions. Moreover, all the materials evidenced fast response time and high mechanical and electronics stability. Therefore, we demonstrated as this approach easily allows the synthesis of nanocomposites with improved performances and different sensing properties that can be tuned depending on the needed application with an unprecedent flexibility. Graphical abstract: Image 1 Highlights: Porous piezoresistive nanocomposites with different properties was produced tuning the prepolymer dilution. Higher dilutions allow the synthesis of piezoresistive with better conductivity, sensibility and limit of detections. Lower dilution allows the synthesis of piezoresistive with larger working range and better mechanical strength. All the dilutions allow the synthesis of piezoresistive materials with fast response time and good stability. Hard template fabrication approach can be used to easily produce materials with different piezoresistive properties.